Analisis Hukum Mangalehen Tuhor terhadap Perempuan: Pada Masyarakat Adat Mandailing di Desa Siginduang Kec. Sosa Julu Kab. Padang Lawas - Herman Hasibuan; Rosnidar Sembiring; Maria Maria (Himpunan Ilmu Hukum dan Ilmu Hukum Islam, 2026)
This study explores the Mangalehen Tuhor tradition within the Mandailing indigenous community in Siginduang Village, Sosa Julu, Padang Lawas, as a customary dowry practice in traditional marriage. The tradition reflects the Mandailing people’s social and moral values rooted in the Dalihan Na Tolu philosophy. However, its implementation often creates gender inequality, especially when women must return twice the dowry upon marriage annulment. This situation illustrates unequal roles between men and women in the customary system. The study emphasizes the need to reinterpret customary law to promote justice, equality, and women’s dignity.